Topological Polynomials and Indices of Line Graphs of Wheel Graphs - Ryabov, Vladislav (Journal of Educational Research and Policies, 2025)
First Zagreb polynomial of a graph G with vertex set V(G) and edge set E(G) is defined as and the first Zagreb index can be obtained from its polynomial as . In this paper some topological polynomials and their indices are obtained for line graph of wheel graph.